Operating with External Arguments of Douady and Hubbard - G. Pastor; M. Romera; G. Alvarez; J. Nunez; D. Arroyo; F. Montoya (Discrete Dynamics in Nature and Society)
The external arguments of the external rays theory of Douady and Hubbard is a valuable tool in order to analyze the Mandelbrot set, a typical case of discrete dynamical system used to study nonlinear phenomena. We suggest here a general method for the calculation of the external arguments of external rays landing at the hyperbolic components root points of the Mandelbrot set. Likewise, we present a general method for the calculation of the external arguments of external rays landing at Misiurewicz points.